2001
DOI: 10.1530/rep.0.1210745
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effect of heat stress on steroid production in medium-sized and preovulatory bovine follicles

Abstract: During the autumn, the conception rate of dairy cattle in warm countries is low although ambient temperatures have decreased and cows are no longer exposed to summer thermal stress, indicating that there may be a delayed effect of heat stress on cattle fertility. Two experiments were conducted to examine possible delayed effects of heat stress on follicular characteristics and steroid production at two distinct stages of follicular growth: medium-sized and preovulatory follicles, 20 and 26 days after heat expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 2 publications
5
112
0
14
Order By: Relevance
“…Some researchers reported that high environment temperature influences the endocrine activity and decreases the oestrus expression (LEE 1993, WOLFENSON et al 1997, ROTH et al 2001. In this study oestrus occurrence was positively correlated with environment temperature and the increase in the environment temperature up to 23 °C did not cause a suppressive effect on the ovarian activity.…”
Section: Discussionsupporting
confidence: 45%
“…Some researchers reported that high environment temperature influences the endocrine activity and decreases the oestrus expression (LEE 1993, WOLFENSON et al 1997, ROTH et al 2001. In this study oestrus occurrence was positively correlated with environment temperature and the increase in the environment temperature up to 23 °C did not cause a suppressive effect on the ovarian activity.…”
Section: Discussionsupporting
confidence: 45%
“…Although this hypothesis was never tested with regard to the NEB challenge, it was found to be true for cows undergoing a short period of heat stress (Roth et al, 2001a and2001b) and can explain the effects of prepartum IGF-I on postpartum follicle development observed in this study.…”
Section: Discussionmentioning
confidence: 76%
“…In another study, Roth et al, [6], indicate that exposing domestic female mammals during heat stress is altered follicular dynamics and lowers the follicular dominance in the next cycle. In 1997, Wolfensohn et al, [10] argued that the preovulatory follicle is a key component in the reproductive system and the deterioration of their function during heat stress may trigger other reproductive effects, such as distortion in gonadotropin secretion, underdevelopment of the body luteum and embryo, resulting in a low fertility.…”
Section: Types Of Stress Caloricmentioning
confidence: 94%
“…Recent studies conducted by Roth et al, [6], mentioned for the first time, evidence of the delayed effect of heat stress on follicular steroidogenesis revealed that exposure of female domestic heat stress led to a decrease in steroidogenesis, 20 and 26 days later, in mid-sized preovulatory follicles. Furthermore, the theca cells more susceptible found that granulose cells and they expressed low estrogen production in medium-sized follicles and low viability in preovulatory follicles.…”
Section: Types Of Stress Caloricmentioning
confidence: 98%